Regenerated UHPC steel fiber stripping method
Through calcination-freezing cycle treatment and subsequent ball grinding, acid decomposition, high-frequency vibration and magnetic separation, the problem of strong bonding between steel fibers and substrates in UHPC is solved, and efficient steel fiber separation and recycling are achieved.
Patent Information
- Application Number
- CN202411788261.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-06
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2044-12-06
AI Technical Summary
The prior art is difficult to effectively remove the strong bond between steel fibers and the matrix in ultra-high performance concrete (UHPC), which makes it difficult to regenerate and recycle the steel fibers.
The calcination-freezing cycle treatment method is used to increase internal defects of the matrix and reduce the bonding force. Then the steel fibers are separated by ball milling, acid decomposition, high-frequency vibration and magnetic separation.
It realizes efficient separation of steel fibers, with a separation efficiency of more than 95%, and maintains more than 80% of steel fibers, reducing overall process energy consumption.
Smart Images

Figure CN119588732A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of solid waste resource utilization, and specifically relates to a stripping method for regenerated UHPC steel fibers. Background Art
[0002] Ultra-high performance concrete (UHPC) is currently widely used in the preparation of large-span pedestrian bridges, highway and railway bridges, thin-walled silos, nuclear waste tanks, cable anchor reinforcement plates, ATM machine protective shells, etc. due to its ultra-high mechanical properties, durability and toughness. In addition, ultra-high performance concrete is considered to be an important low-carbon emission engineering structural material due to its high specific strength and durability, and will receive more extensive attention and application in the domestic engineering field in the future. As an important component of UHPC, steel fiber has the function of significantly increasing the toughness and mechanical properties of UHPC components. Moreover, it is the most expensive raw material in the preparation of UHPC. In the preparation of UHPC, the cost of steel fiber accounts for more than half of the cost of UHPC materials. With the acceleration of the promotion and application of UHPC in the engineering field, it will inevitably bring about the contradiction between construction waste and the depletion of natural resources and environmental pollution in a few years, just like ordinary concrete. Therefore, strengthening the recycling of recycled UHPC, especially the recycling of steel fibers in recycled UHPC, will effectively solve the above problems.
[0003] However, due to its high matrix strength and strong bonding force, UHPC makes the steel fiber bonded to the matrix very firmly, and it is much more difficult to peel it from the matrix than ordinary fiber concrete. At present, although there are studies on the comprehensive utilization of recycled UHPC, there are very few related studies, especially on the stripping method of recycled UHPC steel fiber. Therefore, the development of an effective stripping method for recycled UHPC steel fiber is of great significance to improve the recycling of steel fibers in recycled UHPC. Summary of the invention
[0004] In view of the problems of the prior art, the present invention provides a stripping method for regenerated UHPC steel fibers. By means of calcination-freezing cycle treatment, the internal defects of the matrix are increased to destroy its dense structure, thereby achieving the purpose of weakening the bonding force between the hardened slurry and the fibers in the matrix and reducing the crushing energy consumption of the matrix. Then, the steel fibers are separated from the mixed material by ball milling, acid hydrolysis, high-frequency vibration and magnetic separation. The separation efficiency can reach more than 95%, and the integrity of more than 80% of the steel fibers can be maintained.
[0005] In order to achieve the above purpose, the technical solutions adopted are as follows:
[0006] A stripping method for regenerated UHPC steel fiber comprises the following steps:
[0007] S1. Obtain the strength of the regenerated UHPC matrix;
[0008] S2, calcining the regenerated UHPC in a high temperature furnace, wherein the calcination temperature and time are determined according to the strength of the regenerated UHPC matrix;
[0009] S3, soaking the calcined regenerated UHPC in a mixed aqueous solution of NaCl-sugar, freezing, drying, and then calcining in a high-temperature furnace, and repeating this cycle N times, 2≤N≤5;
[0010] S4, using a ball mill to grind the regenerated UHPC after cyclic calcination and freezing;
[0011] S5, acid-hydrolyzing the crushed regenerated UHPC, and then washing and drying to obtain a mixed material;
[0012] S6. The mixed material is screened by high-frequency vibration and then magnetically separated to obtain regenerated UHPC steel fiber.
[0013] In view of the dense structure of UHPC, the present invention first calcines the regenerated UHPC to generate initial defects inside it, and then soaks it in a NaCl-sugar mixed aqueous solution. The NaCl-sugar mixed aqueous solution penetrates into the internal defects of the calcined regenerated UHPC. In the subsequent freezing process, the NaCl and sugar crystals in the NaCl-sugar mixed aqueous solution produce salt swelling and crystal swelling, which cooperate with the frost swelling in the freezing process to effectively destroy the regenerated UHPC matrix. At the same time, when the frozen regenerated UHPC enters the next stage of calcination, it adheres to the internal defects of the regenerated UHPC matrix. The high temperature decomposition of white sugar produces CO2 and water vapor, which can further produce high temperature cavitation on the regenerated UHPC matrix, so that the regenerated UHPC matrix is further damaged. In this way, the bonding force between the hardened slurry and the fiber in the matrix is effectively weakened, and the subsequent crushing energy consumption of the matrix is reduced. Then, the hardened slurry in the matrix is separated from the fiber by ball milling. Subsequently, the UHPC residue adhering to the steel fiber is removed by acid hydrolysis and the steel fiber rust caused by the calcination-freezing cycle treatment process is eliminated. Finally, the steel fiber is separated from the mixed material by a combination of high-frequency vibration and magnetic separation. The whole process of the present invention can ensure that the steel fiber is effectively separated from the matrix and maintain the integrity of more than 80% of the steel fiber.
[0014] Optionally, obtaining the strength of the regenerated UHPC matrix in step S1 includes:
[0015] The wear amount of UHPC specimens with different strengths was measured using a steel wheel wear tester, and a relationship curve between the strength and wear amount of UHPC specimens was established. The wear amount satisfies the following formula:
[0016] A=M / B×10 3 ;
[0017] Where A is the wear amount, m 3 ; B is the bulk density of UHPC specimen, kg / m 3 ; M is the mass loss of UHPC specimen before and after wear, g;
[0018] The wear amount of the regenerated UHPC matrix was measured using a steel wheel wear tester. The strength of the regenerated UHPC matrix was determined based on the wear amount of the regenerated UHPC matrix and the relationship curve between the strength and wear amount of the UHPC specimen.
[0019] Optionally, the strength and wear relationship curve of the UHPC specimen meets the following conditions:
[0020] fcu,k=118.6kA-0.513, where fcu,k is the strength of the UHPC specimen, MPa; A is the wear amount of the UHPC specimen, m 3 ; k is the correction coefficient, which is 1.03-1.11.
[0021] According to the ultra-high strength and high toughness characteristics of UHPC, the present invention takes the wear amount as an evaluation index, establishes a relationship curve between the strength and the wear amount of the UHPC specimen, and can accurately and quickly obtain the strength of the regenerated UHPC specimen.
[0022] Optionally, the calcination temperature and time in step S2 are determined according to the strength of the regenerated UHPC matrix, including:
[0023] When the strength of the regenerated UHPC matrix is ≤140MPa, the calcination temperature is 500-550°C and the calcination time is 2-3h;
[0024] When 140MPa<the strength of the regenerated UHPC matrix≤180MPa, the calcination temperature is 650-700℃ and the calcination time is 2-3h;
[0025] When the strength of the regenerated UHPC matrix is greater than 180 MPa, the calcination temperature is 800-850° C. and the calcination time is 2-3 h.
[0026] The higher the strength of the UHPC matrix, the higher its ability to withstand high temperature damage. Based on this, the present invention uses different temperature ranges to process UHPC of different strength levels, which can effectively reduce the overall processing energy consumption of the matrix while increasing the internal defects of the matrix.
[0027] Optionally, in step S3, when the strength of the regenerated UHPC matrix is less than 180 MPa, 2≤N≤3; when the strength of the regenerated UHPC matrix is greater than or equal to 180 MPa, 3<N≤5.
[0028] Optionally, the mass concentration of the NaCl-sugar mixed aqueous solution in step S3 is 6-10%, and the mass ratio of NaCl to sugar is (1-2): 1. The freezing temperature in step S3 is -5°C to -10°C.
[0029] The present invention accurately controls the number of calcination-freezing cycles according to the different strength levels of the UHPC matrix, which can further reduce the overall processing energy consumption of the matrix while increasing the internal defects of the matrix.
[0030] Optionally, in step S4, the rotation speed of the ball mill is 60-80 rpm, the ball milling crushing time is 10-15 min, the ball milling medium is a steel ball, and the gradation of the ball milling medium is 80 mm: 50 mm: 30 mm = 1: 1.5-2.0: 0.8-1.
[0031] According to the degree of damage of the regenerated UHPC after cyclic calcination and freezing, the present invention optimizes the ball milling conditions of ball milling crushing, especially the graded composition of the ball milling medium, which can reduce the damage of the steel fiber and improve the integrity rate of the steel fiber while hardening the slurry and the steel fiber in the separation matrix.
[0032] Optionally, the acid hydrolysis temperature in step S5 is 30-40° C., and the acid hydrolysis solution is preferably hydrochloric acid with a mass concentration of 10-20%.
[0033] Optionally, the vibration frequency of the high-frequency vibration in step S6 is 50 Hz-70 Hz, the vibration screening time is 10-20 min, and the sieve hole diameter is 0.10-0.20 mm.
[0034] After the regenerated UHPC of the present invention is subjected to cyclic calcination and freezing treatment, ball milling and crushing, and acid hydrolysis, the steel fibers are separated from the regenerated UHPC matrix, and most of the hardened slurry constituting the regenerated UHPC matrix becomes particles smaller than 1.18 mm. At the same time, the diameter of the steel fibers commonly used in UHPC is 0.15-0.25 mm, the length of the steel fibers is 10-20 mm, and the aspect ratio is 55-70. Based on this, the screening conditions of the present invention preferably use high-frequency vibration screening to ensure that the steel fibers and the coarse particles of the hardened slurry can be effectively retained on the screen, while the fine particles of the hardened slurry are screened out, so as to avoid the presence of fine particles affecting the subsequent magnetic separation effect.
[0035] Compared with the prior art, the present invention has the following beneficial effects:
[0036] 1. The present invention increases the internal defects of the matrix and destroys its dense structure through a modified calcination-freezing cycle treatment method, thereby achieving the purpose of weakening the bonding force between the hardened slurry and the fiber in the matrix and reducing the crushing energy consumption of the matrix. Then, the steel fiber is separated from the mixed material through ball milling, acid hydrolysis, high-frequency vibration and magnetic separation. The whole process of the present invention can ensure that the steel fiber is effectively separated from the matrix, and its separation efficiency can reach more than 95%, and can maintain the integrity of more than 80% of the steel fibers.
[0037] 2. The present invention can effectively reduce the energy consumption of the entire process by optimizing the process parameters, and the present invention fills the gap in the existing research on the separation process of recycled UHPC steel fibers, and provides effective support for the resource utilization of recycled UHPC. At the same time, the particle size of the recycled UHPC obtained by the present invention is basically less than 1.18 mm, which meets the current grading requirements of UHPC aggregates. When it is used for UHPC aggregates, it can reduce the cost of UHPC preparation and solve the problem of shortage of natural aggregate resources. BRIEF DESCRIPTION OF THE DRAWINGS
[0038] Figure 1 : Benchmark relationship curve between strength and wear amount of UHPC specimens. DETAILED DESCRIPTION
[0039] In order to better understand the present invention, the content of the present invention is further explained below in conjunction with specific examples, but the content of the present invention is not limited to the following examples.
[0040] Example 1
[0041] A method for stripping regenerated UHPC steel fibers comprises the following steps:
[0042] S1. Obtain the strength of the regenerated UHPC matrix;
[0043] S2, calcining the regenerated UHPC in a high temperature furnace, wherein the calcination temperature and time are determined according to the strength of the regenerated UHPC matrix;
[0044] S3, soaking the calcined regenerated UHPC in water in a NaCl-sugar mixed aqueous solution, freezing, drying, and then calcining in a high-temperature furnace, and repeating this process N times, 2≤N≤5, wherein the mass concentration of the NaCl-sugar mixed aqueous solution is 6-10%, and the mass ratio of NaCl to sugar in the NaCl-sugar mixed aqueous solution is (1-2):1; the freezing temperature is -5°C to -10°C;
[0045] S4, using a ball mill to ball mill the regenerated UHPC after cyclic calcination and freezing, wherein the rotation speed of the ball mill is 60-80rpm, the ball milling time is 10-15min, the ball milling medium is steel ball, and the gradation of the ball milling medium is 80mm:50mm:30mm=1:1.5-2.0:0.8-1;
[0046] S5, acid-hydrolyzing the crushed regenerated UHPC, and then washing and drying to obtain a mixed material, wherein the acid-hydrolysis temperature is 30-40° C., and the acid-hydrolysis liquid is hydrochloric acid with a mass concentration of 10-20%;
[0047] S6. Screening the mixed material by high-frequency vibration, and then magnetically separating it to obtain regenerated UHPC steel fiber, wherein the vibration frequency of the high-frequency vibration is 50 Hz-70 Hz, the vibration screening time is 10-20 min, and the sieve hole diameter is 0.10-0.20 mm.
[0048] In this embodiment, step S1 specifically includes: using a steel wheel wear tester to measure the wear amount of UHPC specimens with different strengths, and establishing a relationship curve between the strength and the wear amount of the UHPC specimens, wherein the wear amount satisfies the following formula:
[0049] A=M / B×10 3 , where A is the wear amount, m 3 ; B is the bulk density of UHPC specimen, kg / m3; M is the mass loss of UHPC specimen before and after wear, g;
[0050] The relationship curve between the strength and wear of the UHPC specimen meets the following conditions:
[0051] fcu,k=118.6kA-0.513, where fcu,k is the strength of the UHPC specimen (MPa), A is the wear amount of the UHPC specimen, and k is the correction coefficient, which is 1.03-1.11. It is mainly determined based on the difference between the measured strength and the strength label of UHPC of different strength grades and the difference between the measured bulk density and the empirical bulk density average; the wear amount of the regenerated UHPC matrix is measured using a steel wheel wear tester; the strength of the regenerated UHPC matrix is determined based on the wear amount of the regenerated UHPC matrix and the relationship curve between the strength and wear amount of the UHPC specimen.
[0052] Moreover, in this embodiment, step S2 specifically includes:
[0053] When the strength of the regenerated UHPC matrix is ≤140MPa, the calcination temperature is 500-550°C and the calcination time is 2-3h; when 140<the strength of the regenerated UHPC matrix is ≤180MPa, the calcination temperature is 650-700°C and the calcination time is 2-3h; when the strength of the regenerated UHPC matrix is >180MPa, the calcination temperature is 800-850°C and the calcination time is 2-3h.
[0054] Meanwhile, in the present embodiment, in step S3, when the strength of the regenerated UHPC matrix is less than 180 MPa, 2≤N≤3; and when the strength of the regenerated UHPC matrix is greater than or equal to 180 MPa, 3<N≤5.
[0055] Example 2
[0056] A method for stripping regenerated UHPC steel fibers comprises the following steps:
[0057] S1. Obtain the strength of the regenerated UHPC matrix: Prepare UHPC specimens with strength grades of C100, C120, C140, C150, C180, and C220, and measure their bulk density (bulk density = specimen mass / specimen volume); use a steel wheel wear tester with a counterweight of 14 kg, abrasive of 36# brown corundum, and a flow rate of 1 L / min to test the wear of the above UHPC specimens. The test time is 2 minutes, where the wear satisfies the following formula: A = M / B × 10 3 , where A is the wear amount (m 3 ), B is the bulk density of UHPC specimen (kg / m 3 ), M is the mass loss of UHPC specimen before and after wear (g), and the test results are shown in Table 1.
[0058] Table 1
[0059]
[0060]
[0061] The data tested in Table 1 were fitted to establish the relationship curve between the strength and wear of the UHPC specimens. In the process of curve fitting, in order to improve the versatility and accuracy of the fitting curve, the strength fcu,k of the UHPC specimens was first taken according to the strength number, such as the strength of C100UHPC was taken as 100MPa, the strength of C120UHPC was taken as 120MPa, etc., and the measured bulk density of UHPC was taken according to the empirical bulk density of the previous test to obtain the benchmark relationship curve between the strength and wear of the UHPC specimens. Then, according to the relationship between the measured strength of UHPC of different strength grades and the strength number and the relationship between the measured bulk density of UHPC and the mean value of the empirical bulk density in Table 1, the benchmark relationship curve between the strength and wear of the UHPC specimens was corrected; after fitting, the benchmark relationship curve between the strength and wear of the UHPC specimens was obtained, and the fitted benchmark curve diagram is shown in FIG. Figure 1 As shown: f cu,k =118.6A -0.513 , where f cu,k is the strength of UHPC specimen, and A is the wear amount of UHPC specimen.
[0062] The above fitted benchmark relationship curve is corrected, and the corrected UHPC specimen strength and wear relationship curve meets the following conditions: f cu,k =118.6kA -0.513 , where f cu,k is the strength of UHPC specimen, A is the wear amount of UHPC specimen, k is the correction coefficient, which is 1.03-1.11. It is mainly determined based on the difference between the measured strength and strength label of UHPC of different strength grades and the difference between the measured bulk density of UHPC and the average empirical bulk density.
[0063] The strength of the regenerated UHPC matrix was determined according to the wear amount of the regenerated UHPC matrix and the relationship curve between the strength of the UHPC specimen and the wear amount: a number of discarded UHPC plates were selected, and three test pieces (100 mm × 110 mm × 20 mm) were randomly cut out. The wear amount of the three regenerated UHPC matrixes was measured using the above-mentioned steel wheel wear tester. The test results are shown in Table 2.
[0064] Table 2
[0065]
[0066] Substitute the average wear value in Table 2 into formula f cu,k =118.6kA -0.513 , because the sample bulk density is taken as the measured value, the influence of bulk density can be ignored when taking the value of k, and the middle value of 1.07 is taken. According to the above formula, the matrix strength f of the discarded UHPC board can be obtained cu,k =140.5MPa.
[0067] S2. According to the matrix strength fcu,k=140.5 MPa of the discarded UHPC board determined in step S1, the discarded UHPC board is placed in a high-temperature furnace at 650° C. and calcined for 2 h.
[0068] S3, immersing the discarded UHPC board calcined in step S2 in a NaCl-sugar mixed aqueous solution with a mass concentration of 8%, wherein the mass ratio of NaCl to sugar in the NaCl-sugar mixed aqueous solution is 1.5:1, freezing at -8°C for 4 hours, drying at 110°C, and calcining in a high-temperature furnace at 650°C for 2 hours, and repeating this cycle twice.
[0069] S4, using a ball mill to ball mill the waste UHPC board after the cyclic calcination and freezing in step S3, wherein the rotation speed of the ball mill is 60 rpm, the ball milling time is 15 min, the ball milling medium is steel balls, and the gradation of the ball milling medium is 80 mm: 50 mm: 30 mm = 1: 1.5: 0.8.
[0070] S5. The broken waste UHPC board is placed in hydrochloric acid with a temperature of 30°C and a mass concentration of 10% for acid hydrolysis for 20 minutes to fully separate the steel fiber from the UHPC hardened slurry remaining on the steel fiber. After the acid hydrolysis is completed, it is promptly washed with tap water and dried at 110°C to obtain a mixed material.
[0071] S6. The average diameter of the steel fibers in the waste UHPC plates sampled and tested was 0.22 mm, and the average length was 12.33 mm (broken fibers were not removed). Therefore, in this step, a high-frequency vibrating screen with a vibration frequency of 50 Hz and a sieve hole diameter of 0.15 mm was used to screen the mixed material, wherein the vibration screening time was 10 min; a permanent magnet drum magnetic separator was used to magnetically separate the screen material of the high-frequency vibrating screen to obtain recycled UHPC steel fibers.
[0072] In this embodiment, the waste UHPC boards are 5 laboratory-made C140 grade UHPC boards (length 300mm×width 300mm×thickness 20mm), the measured strength is 144.5MPa, the steel fiber content is 2%, the average diameter of the steel fiber used is 0.23mm, the average length is 13.20mm, the total weight of the 5 boards is 21kg, and the total weight of the steel fibers in the 5 boards is 1.4kg. After the above-mentioned waste UHPC boards are treated by the method of this embodiment, the amount of steel fiber recovered is 1.35kg, and the recovery rate is calculated to be 96.4%; 20 recycled steel fibers are randomly selected, and their diameters and lengths are tested, and the test results are shown in Table 3; the average diameter and average length of the remaining steel fibers are calculated by removing the broken steel fibers in Table 3, and the calculation results are shown in Table 4. It can be seen from Tables 3 and 4 that some steel fibers in this embodiment are broken, the steel fiber breakage rate is 15%, and the steel fiber integrity rate is 85%. It shows that the method of the present invention for treating steel fibers has a higher steel fiber integrity retention rate and a higher recovery rate.
[0073] Table 3
[0074] Steel Fiber 1# 2# 3# 4# 5# 6# 7# 8# 9# 10# Diameter / mm 0.24 0.22 0.22 0.21 0.23 0.20 0.23 0.24 0.23 0.23 Length / mm 13.52 13.08 6.85 13.25 13.05 14.15 12.97 13.15 13.02 12.56 Steel Fiber 11# 12# 13# 14# 15# 16# 17# 18# 19# 20# Diameter / mm 0.20 0.23 0.22 0.20 0.20 0.22 0.20 0.21 0.21 0.24 Length / mm 12.87 13.68 12.66 12.85 8.18 13.03 14.64 7.49 12.41 13.17
[0075] Table 4
[0076]
[0077] Furthermore, from the curve fitted in step S1 above, it can be seen that the matrix strength of the discarded UHPC board fcu,k=140.5MPa, which has an error rate of 2.8% and an accuracy of 97.2% compared with the laboratory measured strength of 144.5MPa, indicating that the curve fitted by the present invention has a high accuracy.
[0078] Comparative Example 1
[0079] The difference between this comparative example and Example 2 is that in step S3 of this comparative example, the waste UHPC board calcined in step S2 is soaked in water, and the rest is the same as Example 2. After weighing, the amount of steel fiber recovered in this comparative example is 1.18 kg, and the recovery rate is calculated to be 84.3%. The breakage rate is evaluated according to the method of Example 2, and the steel fiber breakage rate is calculated to be 25%, and the steel fiber integrity rate is 75%.
[0080] The steel fibers recovered from Example 2 and Comparative Example 1 were used to prepare ultra-high performance concrete, and their mechanical properties were tested. The formulation ratios are shown in Table 5 (kg / m 3 ), the mechanical properties test results are shown in Table 6.
[0081] Table 5
[0082] cement Silica Fume Microbeads water Polycarboxylate water reducer Quartz sand Steel Fiber 726 145 166 176 8.3 1037 156
[0083] Table 6
[0084]
[0085] It can be seen from Table 6 that the performance of UHPC prepared by using the steel fiber recycled in Example 2 is equivalent to that of the original steel fiber, and it can replace the original steel fiber for the preparation of UHPC. In Comparative Example 1, the mechanical properties of the steel fiber obtained by directly soaking and freezing the regenerated UHPC with water are lower than those in Example 2, especially the flexural strength. Among them, the flexural strength of the specimen 28d in Comparative Example 1 is reduced by 15.5% compared with the blank sample, while the flexural strength of the specimen 28d in Example 2 is only reduced by 5.5% compared with the blank sample.
[0086] It should be noted that in order to avoid the difference in the bulk density of the specimens caused by the difference in the apparent density of different aggregates, UHPC of the same strength grade in the present invention is prepared using the same type of aggregates.
[0087] The above embodiments are only for illustrating the technical concept and features of the present invention, and their purpose is to enable people familiar with the technology to understand the content of the present invention and implement it accordingly, and they cannot be used to limit the protection scope of the present invention. Any equivalent changes or modifications made according to the spirit of the present invention should be included in the protection scope of the present invention.
Claims
1. A stripping method for regenerated UHPC steel fiber, characterized in that The following steps are involved: S1. Obtain the strength of the regenerated UHPC matrix; S2, calcining the regenerated UHPC in a high temperature furnace; wherein the calcination temperature and time are determined according to the strength of the regenerated UHPC matrix; S3, soaking the calcined regenerated UHPC in a mixed aqueous solution of NaCl-sugar, freezing, drying, and then calcining in a high-temperature furnace; this cycle is repeated N times, 2≤N≤5; S4, using a ball mill to grind the regenerated UHPC after cyclic calcination and freezing; S5, acid-hydrolyzing the crushed regenerated UHPC, and then washing and drying to obtain a mixed material; S6. The mixed material is screened by high-frequency vibration and then magnetically separated to obtain regenerated UHPC steel fiber.
2. The stripping method of regenerated UHPC steel fiber according to claim 1, characterized in that Step S1 includes: The wear amount of UHPC specimens with different strengths was measured using a steel wheel wear tester, and a relationship curve between the strength and wear amount of UHPC specimens was established. The wear amount satisfies the following formula: A=M / B×10 3 ; Where A is the wear amount, m 3 ; B is the bulk density of UHPC specimen, kg / m 3 ; M is the mass loss of UHPC specimen before and after wear, g; The wear amount of the regenerated UHPC matrix was measured using a steel wheel wear tester; the strength of the regenerated UHPC matrix was then determined based on the relationship curve between the strength and wear amount of the UHPC specimen.
3. The stripping method of regenerated UHPC steel fiber according to claim 2, characterized in that The relationship curve between the strength and wear of the UHPC specimen meets the following conditions: f cu,k =118.6kA-0.513, where f cu,k is the strength of UHPC specimen, MPa; A is the wear amount of UHPC specimen, m 3 ; k is the correction coefficient, which is 1.03-1.
11.
4. The stripping method of regenerated UHPC steel fiber according to claim 1, characterized in that Step S2 includes: When the strength of the regenerated UHPC matrix is ≤140MPa, the calcination temperature is 500-550°C and the calcination time is 2-3h; When 140MPa<the strength of the regenerated UHPC matrix≤180MPa, the calcination temperature is 650-700℃ and the calcination time is 2-3h; When the strength of the regenerated UHPC matrix is greater than 180 MPa, the calcination temperature is 800-850° C. and the calcination time is 2-3 h.
5. The stripping method of regenerated UHPC steel fiber according to claim 1, characterized in that Step S3 includes: When the strength of the regenerated UHPC matrix is less than 180 MPa, 2≤N≤3; when the strength of the regenerated UHPC matrix is greater than or equal to 180 MPa, 3<N≤5.
6. The stripping method of regenerated UHPC steel fiber according to claim 1, characterized in that The mass concentration of the NaCl-white sugar mixed aqueous solution in step S3 is 6-10%, and the mass ratio of NaCl to white sugar is (1-2):
1.
7. The stripping method of regenerated UHPC steel fiber according to claim 1, characterized in that The freezing temperature in step S3 is -5°C to -10°C.
8. The stripping method of regenerated UHPC steel fiber according to claim 1, characterized in that In step S4, the rotation speed of the ball mill is 60-80 rpm, the ball milling crushing time is 10-15 min, the ball milling medium is steel ball, and the gradation of the ball milling medium is 80 mm: 50 mm: 30 mm = 1: (1.5-2.0): (0.8-1).
9. The stripping method of regenerated UHPC steel fiber according to claim 1, characterized in that The acid hydrolysis temperature in step S5 is 30-40° C., and the acid hydrolysis solution uses hydrochloric acid with a mass concentration of 10-20%.
10. The stripping method of regenerated UHPC steel fiber according to claim 1, characterized in that The vibration frequency of the high-frequency vibration in step S6 is 50 Hz-70 Hz, the vibration screening time is 10-20 min, and the sieve hole diameter is 0.10-0.20 mm.
Citation Information
Patent Citations
Coarse-aggregate-containing C250-strength-grade ultrahigh-performance fiber concrete and preparation method
CN107285711A
C230-strength-grade ultrahigh-performance fiber reinforced concrete containing coarse aggregates and preparation method of C230-strength-grade ultrahigh-performance fiber reinforced concrete
CN107512887A
Preparation method for steel fiber-rice fiber reinforced expanded perlite luminescent concrete
CN109020321A
3D printed concrete retard-bonded prestress reinforcement component and preparation method thereof
CN111975926A
Interface reinforced recycled aggregate, preparation method thereof and recycled aggregate concrete
CN117303774A